If (9^n×3^2×3^n-27^n)/3^3m ×2^3 =1/27,prove that m - n =1
Attachments:
![](https://hi-static.z-dn.net/files/ddb/b2ddc718f3fbcbbdf3fe7a3d14b3ab56.jpg)
Answers
Answered by
8
by using simple concept of maths
Attachments:
![](https://hi-static.z-dn.net/files/d97/76797c6f79ece73b0b8221ad160aea2c.jpg)
nidhipatilgmailcom:
Thanks
Answered by
1
Answer:
[9^n * 3^2 * {3^(-n/2)^-2 - (27)^n]/3^3m 8 2^3 = 1/27
(3^2n * 3^2 * 3^n - 3^3n)/ 3^3m * 2^3 = 1/27
(3^3n * 3^2 - 3^3n)/ 3^3m = 8/27
3^3n (3^2 - 1)/ 3^3m = 8/27
3^3n (8)/ 3^3m = 8/27
3^3n/ 3^3m = 8/27 * 1/8
3^3n/ 3^3m = 1/27
3^3n/ 3^3m = 3^(-3)
Therefore, 3n-3m = -3
Hence, 3m-3n = 3
It implies 3(m-n) = 3
It implies (m-n) = 3/3
It implies (m-n) = 1
Step-by-step explanation:
Similar questions